Niobium-titanium (Nb-Ti) superconducting joints for persistent-mode operation - Patel, Dipak (Sci Rep, 2019)
Superconducting joints are essential for persistent-mode operation in a superconducting magnet system to produce an ultra-stable magnetic field. Herein, we report rationally designed niobium-titanium (Nb-Ti) superconducting joints and their evaluation results in detail. For practical applications, superconducting joints were fabricated by using a solder matrix replacement method with two types of lead-bismuth (Pb-Bi) solder, including Pb(42)Bi(58) as a new composition. All the joints attained a critical current of >200 A below 1.43 T at 4.2 K. Our optimized superconducting joining method was tested in a closed-loop coil, obtaining a total circuit resistance of 3.25 × 10(−14) Ω at 4.2 K in self-field. Finally, persistent-mode operation was demonstrated in an Nb-Ti solenoid coil with a persistent-current switch. This work will pave the way to developing high-performance Nb-Ti superconducting joints for practical applications.